ARIC Hemostasis Study -II. Organizational Plan and Feasibility Study - Wu, K K; Papp, A C; Patsch, W; Rock, R; Eckfeldt, J; Sharrett, R (Thrombosis and Haemostasis, 1990)
In our previous paper, we reported the development of a blood collection and processing system (BCPS) suitable for the ARIC multicenter hemostasis study. As an additional step of preparation for the ARIC study, we incorporated this BCPS into an organizational plan to increase efficiency and minimize errors. We initially designed organizational trays for blood collection tubes and aliquot tubes and developed a coordinated step-by-step plan for the orderly processing of blood samples. Once the plan was considered workable, we carried out a pilot study to test the feasibility of this integrated organizational plan. Included in the pilot study were 95 healthy subjects randomly selected from 4 ARIC field centers, whose age and gender were comparable to those projected for the ARIC population. We determined the time lapse of filling the first tube as an index of blood flow. The overall mean time-lapse was 23 s (S.D. = 5). There was no significant difference among the field centers. We also determined the entire time lapse required for completing the sample processing. The total processing time was always less than 60 min. By performing the processing of samples in pairs, all the samples from two subjects could be completely processed in 70 min. This greatly increased the efficiency of field center operation. We evaluated the potential in vitro hemostasis activation by measuring plasma Β-thromboglobulin and platelet factor 4 levels. The geometric means of both proteins were comparable to our previously reported results. Fibrinogen, factor VII, factor VIII, von Willebrand factor, antithrombin III, protein C and activated partial thromboplastin time were analyzed. All the hemostatic measurements exhibited no shift of the values. We conclude that the organizational plan together with the BCPS facilitate the incorporation of hemostasis measurements into the ARIC study. It should be valuable as a general guide for other multicenter studies measuring hemostatic factors.